Paradoxes of participatory democracy: citizen participation, collective action and political influence in a Chilean environmental conflict - Matilde Spoerer (Nuevo mundo - Mundos Nuevos, 2014)
This article proposes a critical analysis of the impacts of participatory democracy in public action and collective action. Based on the study of the Barrancones environmental conflict in Chile (2007-2010), the aim is to analyze how transformations and innovations in Chilean environmental law regarding citizen participation have had an ambivalent impact. On one hand, institutional citizen participation appears to be an instrument of economic and authoritarian logic to legitimize energy policy by opening dialogue with citizens without this necessarily translating into decision making. On the other, the institutionalization of citizen participation has had an impact on the emergence and forms of expression of collective action. Thus, participation has influenced both the institutions and their actors. The article reveals the paradoxes of participatory democracy and demonstrates the fact that, based on its institutional implementation, direct and inherent impacts of the participatory mechanism can be identified, as well as broader, diffuse and indirect impacts on public and collective action.